2008
DOI: 10.3354/ame01200
|View full text |Cite
|
Sign up to set email alerts
|

Predation pressure on bacteria increases along aquatic productivity gradients

Abstract: To elucidate how predation pressure on bacteria is affected by increasing productivity in aquatic systems, we ran model simulations of a microbial food web. In addition, we conducted a meta-analysis of data from studies in seas and lakes. The model was run as a flow-through system simulating conditions ranging from oligotrophic to hypertrophic. The organisms included in the model were heterotrophic bacteria, phytoplankton, 3 size classes of protozoa and metazooplankton. Predation pressure was defined as flagel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Meta-analyses of cross-site eutrophication gradients show that planktonic primary production increases linearly with nutrient enrichment, stimulating a linear, but less than 1:1, increase in bacterioplankton production (Cole et al 1988, Thelaus et al 2008. Bacterial biomass, however, increases more slowly than production as a result of increased predation (Thelaus et al 2008). Similar patterns have been observed using experimental mesocosms through the manipulation of primary production (Hobbie & Cole 1984, Oviatt et al 1986) and direct additions of C, N and P (Joint et al 2002, Smith & Prairie 2004, Jansson et al 2006.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Meta-analyses of cross-site eutrophication gradients show that planktonic primary production increases linearly with nutrient enrichment, stimulating a linear, but less than 1:1, increase in bacterioplankton production (Cole et al 1988, Thelaus et al 2008. Bacterial biomass, however, increases more slowly than production as a result of increased predation (Thelaus et al 2008). Similar patterns have been observed using experimental mesocosms through the manipulation of primary production (Hobbie & Cole 1984, Oviatt et al 1986) and direct additions of C, N and P (Joint et al 2002, Smith & Prairie 2004, Jansson et al 2006.…”
Section: Introductionsupporting
confidence: 60%
“…Comparable results for cell density were reported by Mohamed et al (1998) who found that a 15% increment in available DOC led to a 3.6× increment in bacterial density in a heterotrophic biofilm (b~2). A synoptic comparison of 15 marine systems showed that planktonic bacterial biomass and abundance increased only 10× over a 2800× range in primary production (b~0.01) (Thelaus et al 2008). Bacterial productivity was more dynamic, showing a 1000× response in relation to the 2800× change in primary production (b~0.8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, concurrent changes in nutrient availability and predation further complicate interpretion of the effect of predation on a bacterial community (Corno & Jürgens 2008). Modeling results have indicated top-down control of bacterial abundance is more important in eutrophic marine environments (Sanders et al 1992, Thelaus et al 2008). However, a compilation of model and experimental results indicated the opposite: topdown control of marine bacterioplankton abundance was greater in oligotrophic systems (Gasol et al 2002).…”
Section: Discussionmentioning
confidence: 99%